Can The Diamond Fraud Model Influence the Occurrence of Fraudulent Financial Reporting? - Fitrianingsih, Tetiana; Bandi, Bandi (Journal of Asian Multicultural Research for Economy and Management Study, 2024)
This research is quantitative in nature and is intended to examine whether can the diamond fraud model influence the occurrence of fraudulent financial reporting. The fraud diamond theory is measured by pressure (financial stability, financial targets, and external pressure), opportunity (ineffective monitoring), rationalization (change in auditor), and capability (change of director). State-owned business (BUMN) registered on the stock exchange of Indonesia between 2016 and 2022 comprise the population considered within this research. Purposive sampling was utilized in this research to select 154 companies for the sample. In this work, logistic regression analysis is the analytical method. The findings within this research show that the variables of financial stability and financial targets have a significant negative impact on the occurrence of fraudulent financial reporting, while the variables of external pressure and director change do not affect the occurrence of fraudulent financial reporting. The variables of ineffective monitoring and change in auditors also affect the occurrence of fraudulent financial reporting .